Psychological Depth and Moral Collapse: A Dual Reading of All My Sons - Sabri , Fatima; Azeez , Rasha (Al-Adab Journal, 2025)
Arthur Asher Miller (1915-2005) was an American playwright, novelist, and short story writer. His works examine a wide range of social, moral, and psychological themes, often focusing on the human condition, ethical dilemmas, and the consequences of individual actions within a broader societal framework. He was concerned with not only the American man but also the contemporary man in general. By shedding light on the conflicts and turmoils lived by common people in their domestic lives, Miller reflects on how man’s attitude is shaped by society that cares about the outer image of the individual. All My Sons (1949), his first notable work, tackles those themes and reflects the individual’s struggle between oneself and society. This research aims to analyses the psychological aspects of the individual and how societal forces influence one’s life. By applying Carl Gustav Jung’s (1874-1961) concepts of the Archetypes, the individuation process and Jacques Lacan’s (1901-1981) concept of the big Other, the research presents an understanding of the individual and the effect of society upon him. The research presents a comprehensive understanding of the character’s behavior and inner selves. It draws attention to the importance of addressing societal pressures, and how they influence the individual.